Managing a case of acute calculous cholecystitis at home: Highlighting the role of family physicians in providing home-based care - Ashoojit Kaur Anand (Journal of Family Medicine and Primary Care, 2019)
Laparoscopic cholecystectomy is the generally recommended management of acute calculous cholecystitis. It is important for family physicians to be taken into consideration that for some patients the surgical risk–benefit profile favors conservative management. Here, we highlight the possibility of safe, home-based, conservative management of acute calculous cholecystitis in a patient-centered and evidence-based manner by a team of family physicians with backup support of their specialist referral network. We use this case to highlight the value of family physicians providing home-based care.